THE EFFECT OF DRIED RED GINGER EXTRACT POWDER (Zingiber officinale var. rubrum) ON THE LDL, TRIGLYCERIDES and HDL - Oktoviani Oktoviani; Ellen Maidia Djatmiko; Hilda Taurina; Riana Versita (Perkumpulan Dosen Muda Bengkulu, 2021)
Tradisional medicine is a part of Indonesian medicine cukture. As ginger is known to affect blood lipid profile, especially red ginger (Zingiber officinale var. rubrum) with a higher volatile oil content than other types of ginger. Meanwhile, dyslipidemia is a state of abnormal blood lipid profile levels. This research was conducted at RSUD dr. M. Yunus Bengkulu in 2014. Subjects were dyslipidemia with diabetes mellitus type 2 patients in age range 30-60 years. The total subjects in this study were 10 patients with simple random sampling grouping method. Then thay were devided into control group and treatment group. Neither group received standard drug therapy. The dried red ginger powder was only given to the treatment group at a dose of 3 grams per day for one month.. Both groups examined the LDL (Low Density Lipoprotein), trigliseride and HDL (High Density Lipoprotein) levels before and after the study. Changes to LDL, trigliseride and HDL levels were tested by independent sample test with a significance value of p 0.05. From the research that has been done is known that the dried red ginger powder not significantly affect LDL, trigliserida and HDL (p LDL=0,261; p Trigliserida=0,966; p HDL= 0,175). Based on the statistical analysis, it is known that the dried red ginger powder not significantly affect LDL, trigliserida and HDL. Descriptive analysis showed a decrease in triglyceride levels. Deskriptive analysis shows that the dried red ginger powder can inhibit the incerase to LDL, can reduce triglyceride and inhibit the decrease to HDL.